Identification of Glucosinolates in Seeds of Three Brassicaceae Species Known to Hyperaccumulate Heavy Metals. Issue 3 (4th March 2017) - Montaut, Sabine; Guido, Benjamin S.; Grison, Claude; Rollin, Patrick
Abstract : Plants from the Brassicaceae family are known to contain secondary metabolites called glucosinolates. Our goal was to establish by LC/MS the glucosinolate profile of seeds of three Brassicaceae species known to hyperaccumulate heavy metals. We investigated Alyssum fallacinum auct. nonHausskn ., Iberis intermedia Guers ., and Noccaea caerulescens (J.Presl & C.Presl ) F. K.Mey . Our results indicate that A. fallacinum seeds contain glucoiberin and glucoibervirin, which had not been previously identified in this plant. Furthermore, we report for the first time the presence of glucoiberin, glucoibervirin, glucotropaeolin, and sinigrin in I. intermedia . We have detected for the first time glucoconringiin in N. caerulescens . In addition, glucosinalbin, 4‐hydroxyglucobrassicin, and glucomoringin were also detected. Abstract :